Live‐cell screening platform using human‐induced pluripotent stem cells expressing fluorescence‐tagged cytochrome P450 1A1. Issue 7 (18th May 2020) - Kim, Ji‐Woo; Im, Ilkyun; Kim, Hyemin; Jeon, Jang Su; Kang, Eun‐Hye; Jo, Seongyea; Chun, Hang‐Suk; Yoon, Seokjoo; Kim, Jong‐Hoon; Kim, Sang Kyum; Park, Han‐Jin
Abstract: Human‐induced pluripotent stem cells (hiPSCs) are invaluable sources for drug screening and toxicity tests because of their differentiation potential and proliferative capacity. Recently, the CRISPR‐Cas9‐mediated homologous recombination system has enabled reporter knock‐ins at desired loci in hiPSCs, and here, we generated a hiPSC reporter line expressing mCherry‐tagged cytochrome P450 1A1 (CYP1A1), which can be utilized to screen for the modulators of aryl hydrocarbon receptor (AHR) in live cells. CYP1A1‐mCherry hiPSCs exhibited typical characteristics of pluripotent stem cells such as marker expression, differentiation potential, and normal karyotype. After differentiation into hepatocyte‐like cells (HLCs), CYP1A1‐mCherry fusion protein was expressed and localized at the endoplasmic reticulum, and induced by AHR agonists. We obtained 23 hits modulating CYP1A1 expression from high‐content screening with 241 hepatotoxicity chemicals and nuclear receptor ligands, and identified three upregulating chemicals and two downregulating compounds. Responses of hiPSC‐HLCs against an AHR agonist were more similar to human primary hepatocytes than of HepG2 hepatocellular carcinoma cells. This platform has the advantages of live‐cell screening without sacrificing cells (unlike previously available CYP1A1 reporter cell lines), as well as an indefinite supply of cells, and can be utilized in a wide range of screening related to AHR‐ and CYP1A1‐associated diseases in desired cell types.